2013
DOI: 10.1021/ol303510k
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium-Catalyzed Intermolecular [2 + 2] Cycloaddition of Terminal Alkynes with Electron-Deficient Alkenes

Abstract: The first catalytic intermolecular [2 + 2] cycloaddition of terminal alkynes with electron-deficient alkenes is reported. The reaction proceeds with an 8-quinolinolato rhodium/phosphine catalyst system to give cyclobutenes from various substrates having polar functional groups in high yields with complete regioselectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(29 citation statements)
references
References 55 publications
0
29
0
Order By: Relevance
“…Despite the above, access to cyclobutanes by methods other than [2+2]‐photocycloaddition are scarce and in many cases they do not allow complex structures to be built. In addition, the selectivity of [2+2]‐photocycloadditions in solid state is good, provided that the topochemical Schmidt′s conditions are fulfilled, but they usually show a low selectivity in solution . Therefore, the synthesis in solution of cyclobutanes with well‐defined stereochemistry remains a significant challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the above, access to cyclobutanes by methods other than [2+2]‐photocycloaddition are scarce and in many cases they do not allow complex structures to be built. In addition, the selectivity of [2+2]‐photocycloadditions in solid state is good, provided that the topochemical Schmidt′s conditions are fulfilled, but they usually show a low selectivity in solution . Therefore, the synthesis in solution of cyclobutanes with well‐defined stereochemistry remains a significant challenge.…”
Section: Introductionmentioning
confidence: 99%
“…IR (KBr): 2961w, 2939w, 2908w, 2840w, 1654m, 1604m, 1559w, 1507s, 1289m, 1248s, 1180m, 1030s, 899m, 837s = 55.30, 55.33, 87.5, 90.5, 113.7, 114.0, 115.3, 118.1, 127.3, 130.0, 130.1, 133.1, 159.7, 159 2955w, 1732s, 1617m, 1434w, 1418w, 1327s, 1271m, 1251m, 1229w, 1167s, 1109s, 1068s, 1017m, 967w, 908w, 857w, 842m, 828m cm -1 . 13 One-Pot Rhodium-and Palladium-Catalyzed Reaction between Phenylacetylene (1a) and Malonate 5b; Dimethyl 2-(2,4-Diphenylbuta-2,3-dienyl)-2-methylmalonate (7) In a glovebox, Pd(OAc) 2 (1.1 mg, 0.005 mmol, 1 mol%), TDMPP (2.2 mg, 0.005 mmol, 1 mol%), toluene (0.5 mL), and phenylacetylene (1a; 51 mg, 0.5 mmol, 1 equiv) were added into a 10 mL Schlenk tube in this order. The solution was stirred for 1 h, after which a solution of 2 (8.9 mg, 0.025 mmol, 5 mol%) and P(p-anis) 3 (17.8 mg, 0.05 mmol, 20 mol%) in toluene (0.5 mL), CsF (76.0 mg, 0.5 mmol, 1 equiv), and 5b (365 mg, 2.5 mmol, 5 equiv) were added.…”
Section: One-pot Sequential Rhodium-and Palladium-catalyzed Reactionsmentioning
confidence: 99%
“…Our group has recently reported anti-Markovnikov addition of alcohols, 11 secondary amines 12 as well as the [2+2] cycloaddition of electron-deficient alkenes 13 to terminal alkynes catalyzed by 8-quinolinolato rhodium complex systems. During the course of these studies, the formation of alkyne oligomers as by-products was observed.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It should be emphasized that all starting cyclobutenes 1 were prepared by a rhodium-catalyzed intermolecular [2 + 2] cycloaddition of terminal alkynes with electron-deficient alkenes. 15 …”
Section: Introductionmentioning
confidence: 99%